# -5=-5x+3+2

To provide an informative and engaging answer about the equation -5=-5x+3+2 on Quora, let’s break it down step by step:

1. Simplify the equation: -5 = -5x + 3 + 2
2. Combine like terms on the right side: -5 = -5x + 5
3. To isolate the variable (x), let’s move the constant term to the left side by adding 5 to both sides of the equation: -5 + 5 = -5x + 5 + 5Simplifying further: 0 = -5x + 10
4. Now, we can solve for x. To do that, we’ll get rid of the coefficient -5 by dividing both sides of the equation by -5: 0 / -5 = (-5x + 10) / -5Simplifying the equation: 0 = x – 2
5. Therefore, the solution for the equation -5=-5x+3+2 is x = 2.

To help you understand the solution better, here’s an example to illustrate how we arrive at x = 2:

Example: Suppose we substitute x = 2 into the equation -5 = -5x + 3 + 2:

-5 = -5(2) + 3 + 2 -5 = -10 + 3 + 2 -5 = -7 + 2 -5 = -5

As you can see, when x = 2, the equation holds true, and both sides are equal. Therefore, x = 2 is the solution to the equation -5 = -5x + 3 + 2.

I hope this answer helps you understand the equation -5 = -5x + 3 + 2 better! If you have any further questions, feel free to ask.